Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1098/rstb.1996.0045
|View full text |Cite
|
Sign up to set email alerts
|

A structure/function analysis ofEscherichia coliRNA polymerase

Abstract: Control of RNA polymerase is a common means of regulating gene expression. A detailed picture of both the structure and how the structural details of RNA polymerase encode function is a key to understanding the molecular strategies used to regulate RNA polymerase. We review here data which ascribes functions to some regions of the primary sequence of the subunits (alpha, beta beta' sigma) which make up E. coli RNA polymerase. We review both genetic and biochemical data which place regions of the primary sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…RpoS is the sigma factor most closely related to the vegetative RpoD ( 70 ) (28). The two sigmas recognize very similar promoter sequences, which is reflected in a high degree of homology in their 2.4 regions (Fig.…”
Section: Isolation Of Mutations In the Putative Turnover Element Inmentioning
confidence: 99%
“…RpoS is the sigma factor most closely related to the vegetative RpoD ( 70 ) (28). The two sigmas recognize very similar promoter sequences, which is reflected in a high degree of homology in their 2.4 regions (Fig.…”
Section: Isolation Of Mutations In the Putative Turnover Element Inmentioning
confidence: 99%
“…Work from many laboratories has defined the regions within RNA polymerase that are responsible for sequence-specific contacts within promoter DNA. Regions 2.4 and 4.2 of 70 contact the Ϫ10 and Ϫ35 hexamers, respectively (1,2), whereas the C-terminal domain of the ␣ subunit (␣CTD) contacts the UP element (4). Recent work from this laboratory has indicated that a newly defined region of 70 , region 2.5, is responsible for making sequence-specific contacts with the extended Ϫ10 motif (12).…”
mentioning
confidence: 99%
“…E. coli uses a single core RNA polymerase for transcription elongation with subunit composition ␣ 2 ␤␤Ј. Promoter specificity is principally afforded by a separate subunit, , which associates with the core enzyme to give holoenzyme (RNAP) 1 but dissociates once sequence-specific promoter DNA contacts are no longer required (1). The 70 subunit, encoded by rpoD, is one of several subunits utilized by E. coli and is responsible for directing the transcription of most genes during vegetative growth.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The latter, being heterotetramers of the composition (␣) 2 ␤␤Ј, resemble eucaryal RNA polymerases in their overall appearance (3)(4)(5)(6) and in the structural core composition, with the two largest procaryal subunits, ␤ and ␤Ј, having fairly conserved eucaryal orthologs, represented by yeast Rpb1 and Rpb2 (reviewed in Ref. 7). Less obvious homology was noted between eubacterial ␣ subunit and yeast Rpb3 (8), consistent with the reported functional equivalence of ␣ 2 and (Rpb3) 2 dimers in assembly of their respective enzymes (9).…”
mentioning
confidence: 99%